Training and low-cost tech cut aflatoxin by 53 per cent - Hoffmann, Vivian (2020)
Aflatoxin is a common fungal toxin that poses a significant threat to health and economic growth in many developing countries. It is a challenge in Africa, especially in maize and groundnut, which are grown for sale and home consumption by millions of farmers.